Three new species, new records and notes on the nursery-web spider genus Architis in Brazil (Araneae: Pisauridae) - Santos, Adalberto J. (Zootaxa, 2020)
Three new species of the nursery-web spider genus Architis Simon, 1898 are described and illustrated; all collected during spider biodiversity inventories in the Brazilian Amazonia. Architis gracilis Santos sp. nov. is based on a male and A. catuaba Santos sp. nov. on a female specimen, both from the state of Acre, western Brazilian Amazonia. Architis neblina Santos & Nogueira sp. nov. is described from eight females from the Pico da Neblina National Park, state of Amazonas. New records from Brazil are listed for Architis brasiliensis (Mello-Leitão, 1940), A. helveola (Simon, 1898), A. maturaca Santos, 2007 and A. tenuipes (Simon, 1898). The presence of cuspule-like spines on male coxae I, once known only for Architis tenuis Simon, 1898 and A. cymatilis Simon, 1898, are reported for A. maturaca. A remarkable dimorphism in the epigynum of Architis capricorna Carico, 1981 is described based on specimens from southern Brazil. An updated identification key for species of Architis is provided. Copyright © 2008 Magnolia Press.